Relationship between anthropometric and physiological characteristics in youth soccer players - Wong, P. -L.; Chamari, K.; Dellal, A.; Wisloff, U. (The Journal of Strength and Conditioning Research, 2009)
This study examined the relationship between anthropometric and physiological performances among youth soccer players and the positional differences for these variables. Seventy U14 male soccer players (goalkeeper: 10, defender: 20, midfielder: 25, and forward: 15) participated in this study. Body mass was significantly (p < 0.05) correlated with ball shooting speed (r = 0.58) and 30 m sprint time (r = -0.54). Body height was significantly (p < 0.05) correlated with vertical jump height (r = 0.36), 10 m (r = -0.32) and 30 m (r = -0.64) sprint times, Yo-Yo intermittent endurance run (YYIER) distance (r = 0.26), and running time during maximal oxygen uptake (Vo2max) (r = 0.35). Body mass index (BMI) was significantly (p < 0.05) correlated with ball shooting speed (r = 0.31), 30 m sprint time (r = -0.24), Hoff test dribble distance (r = -0.29), YYIER distance (r = -0.25), submaximal running cost (r = -0.38), Vo2max (r = -0.42), and the corresponding running time (r = -0.24). Significant positional differences were observed in anthropometry (body mass [p < 0.01], height [p < 0.01], and BMI [p < 0.01]) but not in physiological performances. This study provides a scientific rationale behind the coaches' practice of selecting young soccer players according to their anthropometry for short-term benefits such as heavier players for higher ball shooting speed and 30-m sprint ability as an example. However, this does not justify such practice in the long-term process of player development.